RADI-33. DISTRIBUTED FRAMELESS GAMMA KNIFE RADIOSURGERY: A NEW TREATMENT PARADIGM FOR PATIENTS WITH BRAIN METASTASES. (12th August 2019) - Patel, Ankur; Mendel, Jameson; Plitt, Aaron; Nedzi, Lucien; Timmerman, Robert; Dan, Tu; Barnett, Samuel; Mickey, Bruce; Patel, Toral; Wardak, Zabi
Abstract: INTRODUCTION: Stereotactic radiosurgery (SRS) has excellent efficacy for patients with limited intracranial disease. Its use in patients with >10 brain metastases remains controversial. Nonetheless, cancer patients are living longer due to advancements in systemic therapeutics and avoiding the neurocognitive toxicities of whole brain radiation therapy is critical. Recent reports suggest that SRS may be effective in patients with ≥10 metastases. Treating large numbers of brain metastases in a single Gamma Knife radiosurgery (GKRS) treatment session poses several challenges. Treatment of metastases in close proximity to one another leads to an increased dose to normal brain, potentially increasing the risk of necrosis. Furthermore, single session treatment of multiple metastases may last several hours, causing significant patient discomfort. Here, we describe a novel treatment paradigm to address these issues: distributed frameless GKRS. Patients with ≥6 brain metastases undergo multi-session frameless GKRS with both temporal and spatial distribution over 2–5 sessions, decreasing treatment time per day and not treating adjacent metastases simultaneously. METHODS: We evaluated all patients with brain metastases who underwent distributed frameless SRS, using the Gamma Knife ICON, between January 2017 and November 2018. Fifty-one patients with 1097 unique lesions were included in this analysis. RESULTS: Mean patient age was 58.8 (range 29–89) years. Median follow-up was 4.1 (range: 0–20.4) months. The median number of metastases treated was 5 (range: 1–19) per treatment session and 11.5 (range: 3–82) per treatment course. The median number of treatment sessions per treatment course was 3 (range: 2–10). The median number of treatment courses, per patient, was 1 (range: 1–4). The median margin dose was 15 Gy. The median overall survival was 5.9 (range: 0.2–20.9) months. CONCLUSIONS: Distributed frameless Gamma Knife radiosurgery is technically feasible and should be considered in lieu of single session GKRS for patients with ≥6 brain metastases.